Efficacy of bacteriophages with Aloe vera extract in formulated cosmetics to combat multidrug-resistant bacteria in skin diseases - Sodaf A. Maan; Abeer A. Faiesal; Gamar M. Gamar; Noha K. El Dougdoug (Scientific Reports)
Abstract Phage therapy offers a promising alternative to antibiotic treatment for combating illnesses caused by multidrug-resistant bacteria. In this study, pathogenic bacteria Staphylococcus aureus and Pseudomonas aeruginosa were isolated from pus and skin infected fluidsusing selective media. These bacterial isolates were biochemically identified as S. aureus and P. aeruginosa with probabilities of 98% and 99%, respectively, through VITEK2 system, and were confirmed as multidrug-resistant based on minimum inhibitory concentration test using colorimetric reagent cards. Lytic phages specific to these isolates were isolated, identified through plaque assays, transmission electron microscopy and classified morphologically according to the new International Committee on Taxonomy of Viruses classification as members of the Straboviridae, Drexlerviridae, and Autographiviridae families. A cosmetic gel formulation combining Aloe vera extract and the phage cocktail was prepared and tested. This gel significantly enhanced phage longevity and reduced bacterial growth by 95.5% compared to the reductions of 90.5% with Aloe Vera extract alone and 45.7% with the basic cosmetic gel. The phage remained effective for 4 to over 12 weeks after being preserved in the cosmetic formula, maintaining populations ranging from 5 × 103 to 25 × 104 PFU/mL in vitro. These findings highlight the potential of phage-based formulations, such as Vena Skin Gel, as innovative biotherapeutic tools for managing skin infections.